2014
DOI: 10.1002/hep.26930
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Niemann-Pick-type C1-like1 by ezetimibe activates autophagy in human hepatocytes and reduces mutant α1-antitrypsin Z deposition

Abstract: Autophagy can degrade aggregate-prone proteins, but excessive autophagy can have adverse effects. It would be beneficial if autophagy could be enhanced in a cell typespecific manner, but this has been difficult because the basic mechanism of autophagy is common. In the present study we found that inhibition of Niemann-Pick-type C1-like 1 (NPC1L1) by ezetimibe activates autophagy only in hepatocytes and small intestinal epithelia, but not in other cells. Ezetimibe induced accumulation of free cholesterol in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 39 publications
(65 reference statements)
2
28
0
Order By: Relevance
“…Although the mechanism of this effect was not elucidated, it was independent of mTOR pathway. Another drug that has recently been shown to activate autophagy specifically is the cholesterol-lowering agent ezetimibe [28]. This drug was investigated by Yamamura et al because cholesterol depletion had an effect on autophagy.…”
Section: New Autophagy Enhancer Strategies For Treatment Of Atd LImentioning
confidence: 99%
See 2 more Smart Citations
“…Although the mechanism of this effect was not elucidated, it was independent of mTOR pathway. Another drug that has recently been shown to activate autophagy specifically is the cholesterol-lowering agent ezetimibe [28]. This drug was investigated by Yamamura et al because cholesterol depletion had an effect on autophagy.…”
Section: New Autophagy Enhancer Strategies For Treatment Of Atd LImentioning
confidence: 99%
“…The studies suggest that, by inhibiting NPC1L1, ezetimibe reduces the recruitment of mTOR to the lysosome and therein inhibits mTORC1 activity to activate autophagy. Most exciting, the authors found that ezetimibe reduces cellular accumulation of ATZ in primary cultures of human hepatocytes engineered for expression of ATZ [28]. …”
Section: New Autophagy Enhancer Strategies For Treatment Of Atd LImentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it must be assumed that EZE may exert a so far unknown hepatic interaction leading to increased DNCS and reduced biliary chol secretion. This may or may not be related to the observation of Yamamura et al [51] that EZE treatment is associated with increased autophagy in human hepatocytes.…”
Section: Scientific Evidence For the Proposed Modelmentioning
confidence: 77%
“…During starvation, about 30% of hepatic proteins are decreased in wild-type mice in 24h of fasting, which becomes insignificant in conditional knockout mice of Atg7 (Mizushima and Klionsky 2007; Komatsu et al 2005). In fact, protein turnover via autophagy is related to multiple hepatic pathophysiological conditions, including the clearance of misfolded mutant proteins in alpha-1-antitrypsin deficiency (Puri and Chandra 2014; Hidvegi et al 2010; Yamamura et al 2014), and in the clearance of the inclusion bodies (Strnad et al 2008; Zatloukal et al 2007; Harada et al 2008). …”
Section: Autophagy: the Basic Processmentioning
confidence: 99%